Molecular Characteristic, Antibiotic Resistance, and Detection of Highly Immunoreactive Proteins of Group B Streptococcus Strains Isolated From Urinary Tract Infections in Polish Adults - Dobrut, Anna; Ochońska, Dorota; Brzozowska, Ewa; Górska, Sabina; Kaszuba-Zwoinska, Jolanta; Gołda-Cępa, Monika; Gamian, Andrzej; Brzychczy-Wloch, Monika (Frontiers in Microbiology, 2022)
Group B streptococcus (GBS) is one of the uropathogens causing urinary tract infections (UTI). The aims of this paper were: molecular characterization, analysis of antimicrobial susceptibility profiles, adherence to bladder endothelial cells, and detection of immunoreactive proteins of 94 clinical strains of GBS isolated from adult Polish patients with UTI. Antibiotic susceptibilities were determined by disc diffusion. Serotyping and Alp family genes detection were studied using multiplex PCR. Genetic profiles were determined by PFGE. Adherence ability of the studied strains was estimated by incubation on HMVEC-Bd cell line. Immunoreactive proteins were studied by immunoblotting. Antibiotic susceptibility investigation revealed that 22% of GBS strains were resistant to erythromycin, whereas 18% demonstrated resistance to clindamycin. cMLSB was present in 76% of the resistant strains, M phenotype was detected in 14%, whereas iMLSB was present for 10%. The most common serotype was serotype III (31%), followed by serotype V (27%), and serotype Ia (17%). Dominant genes among Alp genes were: epsilon (29%), alp2 (27%), and rib (23%). The most common co-occurring serotypes and Alp genes were: Ia and epsilon, III and rib, III and alp2, V and alp2, V and alp3 (p<0.001). The PFGE method showed high clonality for serotype V. Furthermore, this serotype was significantly associated with the cMLSB phenotype (p<0.001). The most common immunoreactive proteins demonstrated masses of 50 kDa, and 45-47 kDa. Although the examined GBS isolates showed high genetic diversity, immunoreactive proteins were shared by most of the studied GBS isolates. It may indicate their conservation, thus allowing to consider them as potential immunodiagnostic markers.